História da cidade de Juazeirinho e sua informalidade imobiliária sob a perspectiva do registro de imóveis - Palmeira, Isailma Abrantes Sátiro (My University, 2025)
Real estate informality in the city of Juazeirinho/PB and the need to regularize properties are the focuses of this dissertation, due to the essentiality of the topic in achieving citizenship and sustainable development, given that the right to adequate housing is a fundamental right. and universal. This topic is directly related to real estate formalization and is strictly related to the Registration and Notarial activity carried out in the city. The general objective is to demonstrate the importance of real estate regularization and how informality negatively impacts the region. The importance of the topic lies in the fact that it is essential to regularize the city's properties, so that Juazeirinhense society can enjoy a sustainable, resilient and suitable urban space for the present and future generations, this being the global goal established by the Nations United in SDG 11, of the 2030 Agenda. In this research, interdisciplinarity is used, as the theme moves between the field of teaching History and Law. Thus, document analysis is the method used together with the experiences within the registry office. We conclude that, through the teaching of history in informal learning spaces and social enlightenment, the city's real estate regularization impacts on sustainable development, since the economic and social benefits are a result of the awareness of the local population. In this way, the following research problem was established: how important is teaching history in raising awareness about real estate regularization in the city of Juazeirinho and what are the positive impacts on the local economy? As a product, a booklet was created aimed at achieving citizens' rights, which promotes awareness of the importance of real estate regularization, aiming to promote the economic development of the region and consequently educate for citizenship. [resumo fornecido pelo autor]
A informalidade imobiliária na cidade de Juazeirinho/PB e a necessidade de regularização dos imóveis são os enfoques desta dissertação, em razão da essencialidade do tema para o alcance do exercício da cidadania e do desenvolvimento sustentável, visto que o direito à moradia adequada é direito fundamental e universal. Este tema possui relação direta com a formalização imobiliária e guarda estrita relação com a atividade Registral e Notarial exercida na cidade. O objetivo geral é demonstrar a importância da regularização imobiliária e como a informalidade impacta negativamente a região. A importância do tema reside no fato de que é imprescindível regularizar os imóveis da cidade, a fim de que a sociedade juazeirinhense possa desfrutar de um espaço urbano sustentável, resiliente e adequado à presente e à futura geração, sendo essa a meta mundial estabelecida pelas Nações Unidas no ODS 11, da Agenda 2030. Nesta pesquisa, é utilizada a interdisciplinaridade, posto que o tema transita entre o campo do ensino da História e do Direito. Assim, a análise documental é o método utilizado juntamente com as experiências vivenciadas dentro do cartório. Concluímos que, por intermédio do ensino da história em espaços informais de aprendizagem e do esclarecimento social, a regularização imobiliária da cidade impacta no desenvolvimento sustentável, posto que os benefícios econômicos e sociais são decorrência da conscientização da população local. Dessa maneira, foi estabelecido o seguinte problema de pesquisa: qual a importância do ensino de história na conscientização da regularização imobiliária na cidade de Juazeirinho e quais os impactos positivos na economia local? Como produto foi elaborada uma cartilha destinada ao alcance dos direitos do cidadão que promove a conscientização sobre a importância da regularização imobiliária, visando o fomento econômico da região e consequentemente educando para a cidadania. [resumo fornecido pelo autor]
Keywords: História local - Juazeirinho (PB); História - Estudo e ensino; Registro de imóveis - Juazeirinho (PB); Cidadania; Local history - Juazeirinho (Brazil); History - Study and teaching; Property registration - Juazeirinho (Brazil); Citizenship